Synthesis and Characterization of TEOS Coating Added With Innovative Antifouling Silica Nanocontainers and TiO2 Nanoparticles - Ruggiero, Ludovica; Fidanza, Maria Rosaria; Iorio, Morena; Tortora, Luca; Caneva, Giulia; Ricci, Maria Antonietta; Sodo, Armida (Frontiers in Materials, 2020)
We study the synthesis and characterisation of an innovative TEOS-based composite coating, which could improve previous formulations used in the field of monument conservation. The proposed coating is composed by a tetraethoxyorthosilicate matrix (TEOS), containing an elasticiser (hydroxyl-terminated polydimethylsiloxane (PDMS-OH)) and a non-ionic surfactant (n-octylamine). The specific self-cleaning and antifouling properties are obtained by the addition of different kinds of nanofillers: the commercial TiO2 nanoparticles, plus two different silica nanocontainers, loaded with the commercial biocide 2-mercaptobenzothiazole. Through a multi-analytical approach, we evaluate the effect of the nanoparticles concentration on the coatings drying rate, on the variation of their visual aspect and textural properties. Our results show that the addition of the silica nanocontainers at 0.05% (w/v) in sol does not change the colour of the coating and reduces the formation of cracks after drying. Moreover, the coating charged with nanocontainers undergoes slower drying, thus improving its penetration into the pores of the treated surface. Further tests of photocatalytic and biocidal properties of this new product on different lithotypes and their potential interactions are in progress.